T(H)17 cells in tumour immunity and immunotherapy - Zou, Weiping (2010)
T helper 17 (T(H)17) cells have well-described roles in autoimmune disease. Recent evidence suggests that this effector T cell subset is also involved in tumour immunology and may be a target for cancer therapy. In this Review, we summarize recent findings regarding the nature and relevance of T(H)17 cells in mouse models of cancer and human disease. We describe the interplay between T(H)17 cells and other immune cells in the tumour microenvironment, and we assess both the potential antitumorigenic and pro-tumorigenic activities of T(H)17 cells and their associated cytokines. Understanding the nature of T(H)17 cell responses in the tumour microenvironment will be important for the design of more efficacious cancer immunotherapies.